If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -4 = 10x + 19 Reorder the terms: -4 + 8x = 10x + 19 Reorder the terms: -4 + 8x = 19 + 10x Solving -4 + 8x = 19 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -4 + 8x + -10x = 19 + 10x + -10x Combine like terms: 8x + -10x = -2x -4 + -2x = 19 + 10x + -10x Combine like terms: 10x + -10x = 0 -4 + -2x = 19 + 0 -4 + -2x = 19 Add '4' to each side of the equation. -4 + 4 + -2x = 19 + 4 Combine like terms: -4 + 4 = 0 0 + -2x = 19 + 4 -2x = 19 + 4 Combine like terms: 19 + 4 = 23 -2x = 23 Divide each side by '-2'. x = -11.5 Simplifying x = -11.5
| 9xz^2-30xz-96x= | | -2x-7(c+3)=-93 | | 1(a-4)=2(2a+4) | | 8x-4=10+19 | | 4-3yi=4x+16i | | -329=-7(7+5p) | | x=0.5+y | | 3(4x-7)=6-(2-5x) | | 8(-8k-1)=5k-8 | | -11=9-2b | | 31=25-x-x | | 4(2x-7)+4=8 | | 3x+4y-z=4 | | 4x+9=10x+3 | | -59=-4n-3 | | 8-3x+2x=3(x+4) | | 25-7v=10(v-6) | | F(x)=105x | | 10y+5x=30 | | 2c+10=c-2 | | -12x=-228 | | 12x+32=10+y | | 2y^2-6x+1=0 | | 3m^3+192= | | -70=14n | | 12(600)=x | | 2(-3x+5)-6x=-3(x+4) | | 14-5x+9x=-2(-7x+3) | | 8n-17=0 | | x^2-2xy+8=0 | | x-9=3x+15 | | -9x+1=2x-8 |